2007
DOI: 10.1002/ceat.200600327
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Liquid Radial Spreading Coefficients of Some Highly Effective Packings

Abstract: The liquid radial spreading coefficient of packings for absorption and rectification columns is necessary to determine the packing height which ensures uniform liquid distribution over the column cross section. The existing calculation methods can be used theoretically only when this coefficient is independent of the liquid superficial velocity, which is often not the case. A tracer method free from this limitation is developed and tested. The spreading coefficients for different sizes of modern, highly effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…where ϕ is the sphericity of the packing. Dzhonova‐Atanasova et al 7 observed similar results regarding the effect of the packing size on the liquid dispersion from their measurements of liquid spreading in a column of 470 mm in diameter packed with several highly effective packings in the absence of gas flow.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…where ϕ is the sphericity of the packing. Dzhonova‐Atanasova et al 7 observed similar results regarding the effect of the packing size on the liquid dispersion from their measurements of liquid spreading in a column of 470 mm in diameter packed with several highly effective packings in the absence of gas flow.…”
Section: Introductionmentioning
confidence: 61%
“…As one of the key parameters affecting the hydrodynamics of trickle‐bed reactors (TBR), dispersion of the liquid across the packed bed usually results from several different mechanisms 1, such as the mechanical dispersion induced by the variation of the microscopic velocity profiles in the porous structures, the capillary dispersion due to capillary pressure gradients, and the interaction forces between different phases 2. The above mechanisms make liquid dispersion a rather complex process, and many variables should be considered in the analysis of liquid dispersion in TBR, such as the gas and liquid velocities 3, 4, the liquid properties 5, the packing shape and size 6, 7, the packing orientation 8, the ratio of the column diameter to the particle diameter 9, the reactor pressure 10, the bed height 11, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have not found other attempts to apply the presented approach for modeling the liquid distribution in a layer of random RSRM packing, which is characterized with "open to flow structure". As reported in Dzhonova et al (2007), these types of packings have many lamellas and distribute liquid flow randomly, on the contrary to the previous generations of older types of packings like Raschig rings, which radial redistribution ability is higher than RSRM.…”
Section: Discussionmentioning
confidence: 79%
“…In the case of unknown value of D for the packing considered, another approach (single jet method) is developed, which is explained in detail in [2], and needs experimental data for radial liquid distribution, measured after relatively short packing layer and at central point initial irrigation. Fortunately, such data was available and we applied the single jet method to determine D for a packing RMSR 70-5.…”
Section: Methodsmentioning
confidence: 99%
“…In the last 10 years, there has only been a limited number of studies about the 4 th generation random packings except our research in this field [3-4, 8-9, 11], which investigate experimentally and model the radial liquid distribution and maldistribution [3][4]9] in those packings. Moreover, there is insufficient information about the radial spreading ability and wall flow effects in these packings [2,7], especially in the column diameters greater than 0.5 m. In contrast, the older type of packings are widely examined in the literature. Therefore, the motivation of our work is to fill the gap and test our models in industrial scale area, based on the existing experimental data for highperformance random packings.…”
Section: Introductionmentioning
confidence: 99%